Research progress on fungal corrosion of metals and their protective layers in atmospheric environments - LIU Qian-qian; LU Lin; GAO Ge; LI Xiao-gang (工程科学学报)
Microorganisms and their characteristic metabolisms seriously affect the service performance and service life of materials. To date, most studies have concentrated on the bacterial corrosion of materials and comparatively few have focused on the corrosion behavior and mechanisms fungi exhibit in atmospheric environments. Many fungi exist in the atmosphere and their activities significantly influence the corrosion of metals and coatings. In this paper, the relationship was reviewed between the biochemical characteristics of fungi and the corrosion behaviors of these materials, the effects of fungal corrosion behavior were discussed on metal and coating materials in atmospheric environments, and the mechanism of fungal corrosion was described. By contrasting the features of two types of corrosion, It was found that fungal corrosion mainly differ from bacterial corrosion with respect to their respective metabolites. Currently, most fungal corrosion research has been limited to phenomenal description and corrosion product analysis and has lacked any quantitative characterization of fungal metabolism and corrosion kinetics, which merits greater emphasis in future research.